2009
DOI: 10.1029/2009gl040367
|View full text |Cite
|
Sign up to set email alerts
|

Does the North Atlantic Oscillation show unusual persistence on intraseasonal timescales?

Abstract: Previous studies have argued that the autocorrelation of the winter North Atlantic Oscillation (NAO) index provides evidence of unusually persistent intraseasonal dynamics. We demonstrate that the autocorrelation on intraseasonal time‐scales of 10–30 days is sensitive to the presence of interannual variability, part of which arises from the sampling of intraseasonal variability and the remainder of which we consider to be “externally forced”. Modelling the intraseasonal variability of the NAO as a red noise pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 14 publications
7
65
1
Order By: Relevance
“…In fact with further analysis (not shown) it is found that τ needs to be longer than ∼ 30 days before the two lines intersect. This is consistent with the south and mid clusters being related to the negative and positive phases of the NAO, which is known to possess a long decorrelation time-scale (Ambaum and Hoskins, 2002;Keeley et al, 2009). By contrast transitions involving the north cluster (P S→N , P M→N , P N→S , P N→M , P N→N ) approach very close to or intersect the climatological occupancy within 15 days.…”
Section: Comparison Of 'Climatological' Transition Probabilities Fromsupporting
confidence: 69%
“…In fact with further analysis (not shown) it is found that τ needs to be longer than ∼ 30 days before the two lines intersect. This is consistent with the south and mid clusters being related to the negative and positive phases of the NAO, which is known to possess a long decorrelation time-scale (Ambaum and Hoskins, 2002;Keeley et al, 2009). By contrast transitions involving the north cluster (P S→N , P M→N , P N→S , P N→M , P N→N ) approach very close to or intersect the climatological occupancy within 15 days.…”
Section: Comparison Of 'Climatological' Transition Probabilities Fromsupporting
confidence: 69%
“…This structure is largely consistent with SST regressions over the Sahel index (not shown), although the tropical Pacific signal is stronger here. At lag zero however, a signal similar to the intraseasonal projection of the summer North Atlantic Oscillation (NAO, Keeley et al, 2009;Bladé et al, 2012) appears in the north Atlantic and is significant off North America, suggesting that seasonal variability over west Africa (see Figure 5) is linked to that of the northern Atlantic basin.…”
Section: Oceanic Forcings Of the Wammentioning
confidence: 99%
“…In recent studies, it has been pointed out that the NAO exhibits unusual persistence, as evidenced by a ''shoulder'' of slow decay in the autocorrelation function between 10 and 30 days (e.g., Ambaum and Hoskins 2002;Rennert and Wallace 2009). However, Keeley et al (2009) showed that this shoulder feature is sensitive to the presence of interannual variability, and as such it may not reflect enhanced predictability on intraseasonal time scales. The interannual variability itself is a combination of externally forced variations and variations arising from climate noise: that is, from sampling variability associated with the averaging of shorter time-scale intraannual fluctuations (Feldstein 2000(Feldstein , 2002Franzke 2009;Keeley et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, Keeley et al (2009) showed that this shoulder feature is sensitive to the presence of interannual variability, and as such it may not reflect enhanced predictability on intraseasonal time scales. The interannual variability itself is a combination of externally forced variations and variations arising from climate noise: that is, from sampling variability associated with the averaging of shorter time-scale intraannual fluctuations (Feldstein 2000(Feldstein , 2002Franzke 2009;Keeley et al 2009). The fraction of interannual variability, which is externally forced and hence potentially predictable, is of obvious interest for seasonal and longer-range forecasting.…”
Section: Introductionmentioning
confidence: 99%